Mobility endowment and entitlements mediate resilience in rural livelihood systems. (January 2019) - Tebboth, M.G.L.; Conway, D.; Adger, W.N.
Highlights: Choice in mobility decisions mediates resilience. Households practicing shorter-term, more circular mobility appear more resilient. There is evidence of trade-offs between resilience and wellbeing, especially for some immobile households. Abstract: In economically marginal rural areas, choice in livelihood strategy such as decisions to move location mediates levels of individual and household resilience under conditions of environmental change. It is widely recognised that endowments associated with mobility and the entitlement to mobility are unevenly distributed across populations. This paper integrates these insights and conceptualises location choice as a set of mobility endowments and mobility entitlements. Through focussing on endowments and entitlements, the paper explores how choice affects the ability to be mobile and its role in mediating levels of resilience to livelihood shocks associated with changing environmental conditions. The research design involves measuring the impact of different climatic perturbations in rural locations in Anhui Province, China. Mixed methods of rural appraisal, life history interviews, and a household survey generate objective and perceived elements of individual and household responses to risks. These data are augmented by biophysical observations on the nature of the climatic perturbations. The results show that mobility endowments and mobility entitlements are important in determining the impact of mobility on resilience. The life history interview data highlight significant individual agency within the structures that impact on individual choices. Further, individuals and households who possess the ability to decide and to subsequently enact decisions about mobility, are shown to be more resilient compared to other individuals and households that lack such ability. Moreover, households practicing short-term, circular mobility are more resilient than those households that practice long-term mobility. The study confirms that, in these instances, choice and the ability to enact those choices mediates resilience and highlights the implications of location decisions but also the conditions in which those decisions are made.